Active wild bird surveillance of avian influenza viruses, a report. Issue 12 (22nd December 2022) - Waldenström, Jonas>; van Toor, Mariëlle; Lewis, Nicola; Lopes, Sara; Javakhishvili, Zura; Muzika, Denys; Fouchier, Ron A. M.; Brouwer, Adam
Abstract: This report summarises the potential for an EU‐wide active surveillance of highly pathogenic avian influenza (HPAI) virus in wild birds. As basis for the analyses, we collected and analysed virological and ornithological data and carried out fieldwork in two countries outside the EU: Ukraine and Georgia. We show that it is possible to build capacity and logistics for sampling nodes that can provide rapid detection and identification of HPAI, that are key features for an early warning system. Based on the data presented here, it is suggested that an EU‐level surveillance network in wild birds is constructed, where surveillance nodes are chosen to reflect the epidemiological benefit of the whole EU. Selection of sampling nodes in the surveillance network should incorporate ornithological and virological background data, and that on‐site development should include combined local ornithology and virology expertise and a minimised analytic time frame from sample to result. Ideally, surveillance nodes should be constructed with operational flexibility in what type of material that can be collected, such as active surveillance of wild birds (cloacal, oropharyngeal, blood samples), sampling of hunting bags, and the possibility to take environmental samples or to sample carcasses. This way a surveillance node could be adapted to changes in virus epidemiology, such as shifts in what hosts need to be sampled and at what times of the year sampling should occur. In times of enzootic virus circulation, the network should be tuned to monitor waves of infections and provide warning signals when increased activity is anticipated based on migratory bird movements. Based on the above assumptions, we provide a set of suitable regions, both within and outside the EU, that should be considered.